Insertion of the human immunodeficiency virus CD4 receptor into the envelope of vesicular stomatitis virus particles. - Schubert, M (1992)
Enveloped virus particles carrying the human immunodeficiency virus (HIV) CD4 receptor may potentially be employed in a targeted antiviral approach. The mechanisms for efficient insertion and the requirements for the functionality of foreign glycoproteins within viral envelopes, however, have not been elucidated. Conditions for efficient insertion of foreign glycoproteins into the vesicular stomatitis virus (VSV) envelope were first established by inserting the wild-type envelope glycoprotein (G) of VSV expressed by a vaccinia virus recombinant. To determine whether the transmembrane and cytoplasmic portions of the VSV G protein were required for insertion of the HIV receptor, a chimeric CD4/G glycoprotein gene was constructed and a vaccinia virus recombinant which expresses the fused CD4/G gene was isolated. The chimeric CD4/G protein was functional as shown in a syncytium-forming assay in HeLa cells as demonstrated by coexpression with a vaccinia virus recombinant expressing the HIV envelope protein. The CD4/G protein was efficiently inserted into the envelope of VSV, and the virus particles retained their infectivity even after specific immunoprecipitation experiments with monoclonal anti-CD4 antibodies. Expression of the normal CD4 protein also led to insertion of the receptor into the envelope of VSV particles. The efficiency of CD4 insertion was similar to that of CD4/G, with approximately 60 molecules of CD4/G or CD4 per virus particle compared with 1,200 molecules of VSV G protein. Considering that (i) the amount of VSV G protein in the cell extract was fivefold higher than for either CD4 or CD4/G and (ii) VSV G protein is inserted as a trimer (CD4 is a monomer), the insertion of VSV G protein was not significantly preferred over CD4 or CD4/G, if at all. We conclude that the efficiency of CD4 or CD4/G insertion appears dependent on the concentration of the glycoprotein rather than on specific selection of these glycoproteins during viral assembly.